Anti-Vibration and EPP Insulation Solar Food Delivery / Mohd Sharil Iqmal Mohd Sabri - Mohd Sabri, Mohd Sharil Iqmal (2020)
FDBox Enterprise is sole business which located at Seremban 2, Negeri Sembilan has been chosen since the place is strategic where it is near to the highways. So, it is easier for supplier to deliver raw material and ease customers to get the services. FDBox Enterprise will be launching completely new food delivery box namely Antivibration and EPP Insulation Solar Food Delivery Box. This product is a new product lines and classified as new to the firm under modification category because it is new to the company but not new to marketplace. This Anti-vibration and EPP Insulation Solar Food Delivery Box had made some modification on the existing products that manufactured by other companies by providing improved performance and technology.